Sonic Hedgehog Pathway Modulation Normalizes Expression of Olig2 in Rostrally Patterned NPCs With Trisomy 21 - Klein, Jenny A.; Li, Zhen; Rampam, Sanjeev; Cardini, Jack; Ayoub, Amara; Shaw, Patricia; Rachubinski, Angela L.; Espinosa, Joaquin M.; Zeldich, Ella; Haydar, Tarik F. (Frontiers in Cellular Neuroscience, 2022)
The intellectual disability found in people with Down syndrome is associated with numerous changes in early brain development, including the proliferation and differentiation of neural progenitor cells (NPCs) and the formation and maintenance of myelin in the brain. To study how early neural precursors are affected by trisomy 21, we differentiated two isogenic lines of induced pluripotent stem cells derived from people with Down syndrome into brain-like and spinal cord-like NPCs and promoted a transition towards oligodendroglial fate by activating the Sonic hedgehog (SHH) pathway. In the spinal cord-like trisomic cells, we found no difference in expression of OLIG2 or NKX2.2, two transcription factors essential for commitment to the oligodendrocyte lineage. However, in the brain-like trisomic NPCs, OLIG2 is significantly upregulated and is associated with reduced expression of NKX2.2. We found that this gene dysregulation and block in NPC transition can be normalized by increasing the concentration of a SHH pathway agonist (SAG) during differentiation. These results underscore the importance of regional and cell type differences in gene expression in Down syndrome and demonstrate that modulation of SHH signaling in trisomic cells can rescue an early perturbed step in neural lineage specification.